PENGARUH PERBEDAAN LANTAI DAN KEPADATAN KANDANG TERHADAP PRODUKSI DAN BOBOT TELUR AYAM NIAGA PETELUR - Mohammad luthfi Nur fauzi; Elly Tugiyanti; Imam Suswoyo (ANGON: Journal of Animal Science and Technology, 2022)
Background. The study entitled "The effect of in Type and Density of Cages on egg production and Weight of Commercial Laying Hens" was to determine the effect of floor type and density on egg production of laying hens. and determine the effect of floor type and density on egg weight of laying hens. Materials and Methods. The material used in this study was 120 female Isa Brown laying hens aged 18 weeks and weighing about 1.5 kg. Each treatment unit consisted of 40 slat cages, the slat floor contained 20 laying commercial chickens and 1 commercial laying hens, 20 layers and 40 litter cages, the litter floor contained 20 laying commercial chickens and filled with 1 commercial chicken laying plots of 20 plots with each size of 40x50x30 . This research was conducted using a completely randomized design (CRD) method with 4 treatments and 5 replications. The treatments included (Litter floor with a density of 2 tail), (Littery floor with a density of 1 tail), (Slat floor with a density of 2 tail) and (Slat floor with a density of 1 tail). Results. The results showed that the average egg production in treatments P1, P2, P3, P4 respectively were 33.47 ± 1.9959, 32.14 ± 2.1761, 34.63 ± 2.0667 and 37.39± 2.2468 percent. The average egg weights in treatments P1, P2, P3, P4 respectively were 48 ± 5.27870, 49 ± 8.95229, 50 ± 4.31113 and 51 ± 5.73045 weight/grams. Conclusion. It shows that there is no effect of floor type and cage density on egg production.